Tailoring translational strength using Kozak sequence variants improves bispecific antibody assembly and reduces product‐related impurities in CHO cells. Issue 7 (21st April 2020) - Blanco, Noelia; Williams, Ambrose J.; Tang, Danming; Zhan, Dejin; Misaghi, Shahram; Kelley, Robert F.; Simmons, Laura C.
Abstract: Optimal production of bispecific antibodies (bsAb) requires efficient and tailored co‐expression and assembly of two distinct heavy and two distinct light chains. Here, we describe a novel technology to modulate the translational strength of antibody chains via Kozak sequence variants to produce bsAb in a single cell line. In this study, we designed and screened a large Kozak sequence library to identify 10 independent variants that can modulate protein expression levels from approximately 0.2 to 1.3‐fold compared with the wild‐type sequence in transient transfection. We used a combination of several of these variants, covering a wide range of translational strength, to develop stable single cell Chinese hamster ovary bispecific cell lines and compared the results with those obtained from the wild‐type sequence. A significant increase in bispecific antibody assembly with a concomitant reduction in the level of product‐related impurities was observed. Our findings suggest that for production of bsAb it can be advantageous to modify translational strength for selected protein chains to improve overall yield and product quality. By extension, tuning of translational strength can also be applied to improving the production of a wide variety of heterologous proteins. Abstract : A novel technology to modulate the translational strength of antibody chains via Kozak sequence variants to produce bispecific antibodies in a single cell line was developed in this study. By using this strategy, Blanco and coworkers showed that tuning the translational strength for selected protein chains increases the bispecific antibody assembly with a concomitant reduction in the level of product‐related impurities, improving overall yield and product quality.